2019
DOI: 10.3390/medicina55050138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Consumption of Prickly Pear Cacti (Opuntia spp.) and its Products on Blood Glucose Levels and Insulin: A Systematic Review

Abstract: Background and Objectives: There is confusion as to which component of the Opuntia spp. cacti has demonstrated anti-hyperglycemic effects or anti-diabetic properties. It is important to clarify these health benefits due to the increasing need for prevention and treatment of chronic diseases. The aim of this review is to identify the effects of Opuntia spp. cacti consumption on biomedical measures; glucose and insulin with consideration of its’ components; fruit, leaf and combined or unidentified Opuntia spp. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 50 publications
(157 reference statements)
0
26
0
Order By: Relevance
“…The prickly pear fruit can be considered a healthy fruit, which is a property that has been attributed to its bioactive compounds, mainly represented by polyphenols, flavonoids and pigments such as betalains. Other authors reported the presence of vitamin C, carotenoids and taurine [1][2][3][4]. This fruit showed to be rich in polyphenolic compounds with a more antioxidant effect than vitamins.…”
Section: Introductionmentioning
confidence: 79%
“…The prickly pear fruit can be considered a healthy fruit, which is a property that has been attributed to its bioactive compounds, mainly represented by polyphenols, flavonoids and pigments such as betalains. Other authors reported the presence of vitamin C, carotenoids and taurine [1][2][3][4]. This fruit showed to be rich in polyphenolic compounds with a more antioxidant effect than vitamins.…”
Section: Introductionmentioning
confidence: 79%
“…This indicates that such cacti should not be offered to ruminants as a sole source of food. They should be offered to them in conjunction with other ingredients that can meet the nutrient requirements of the species and the categories of animals (Prieto-Garcia et al, 2016;Gouws et al, 2019). Cavalcanti & Resende (2007), evaluating the effects of the use of C. jamacaru and P. gounellei on the weight gain of goats during drought periods, concluded that the supply of diets composed exclusively of cacti did not meet the nutritional requirements of animals kept in confinement.…”
Section: Discussionmentioning
confidence: 99%
“…accumulate various secondary metabolites with health-promoting effects. Consuming the plant has a beneficial effect on serum glucose and insulin levels and its efficacy in weight management has been demonstrated through in vitro experiments and clinical populations [ 4 , 5 ]. The bioactive compound content varies considerably due to several factors, including genetic profile, phenological stage, and environmental stress exposure [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%